Atenção em atletas de futebol de base em diferentes categorias: comparação e tabela de referência - Daniella Moreira Paína (2018)
Soccer is a sport with high complexity stimuli during the match. Therefore, it is necessary for the athlete to make the best choices when making a play. During the training process the young athletes are prepared to achieve high performance, working their technical, tactical, physical and psychological abilities. Among the psychological abilities, an important cognitive capacity that can contribute in the decision making process of young athletes of soccer of high competitive level is the attention. Attention is the ability to select the relevant stimuli in an environment, helping the athlete to respond in a shorter time and with a better quality in the accuracy of the response. Thus, recognizing the importance of this cognitive ability and seeking to understand its behavior in young soccer athletes of the sub-14, sub-15, sub-17 and sub-20 categories, the objectives of this study were: (a) construct reference tables of attention from the time variables and response accuracy for soccer athletes of income from different base categories; (b) to compare the attention through the response time variable of soccer athletes of income between the different categories; (c) to compare attention through the variable accuracy of soccer athletes' performance response among different base categories. Were evalued 320 athletes (16.5 years +2.09) were evaluated from the young categories of three Brazilian soccer clubs. 77 athletes from the sub-14 category (14.55 years +0.24), 66 athletes from the sub-15 category (15.54 years +0.24), 78 athletes from the sub-17 category (16.79 +0, 46) and 99 athletes of the sub-20 category (18.49 years +2.03). The instruments used were: (a) demographic data questionnaire and (b) Cognitrone Test of the Vienna Test System SPORTS®, which evaluates attention for the variables: response time (measured in seconds) and accuracy of responses. To characterize the sample, descriptive statistics were used with mean, standard deviation, median and interquartile range. The Shapiro-Wilk test was performed for normality analysis. The study data did not present a normal distribution. In the comparison between the categories the Kruskal-Wallis test with Bonferroni correction was used. To order the reference tables, an ordered series percentile and interquartile analysis were used. The COG reliability test was performed using Cronbach's Alpha (). The statistical procedures were calculated in the statistical package SPSS® (Statistical Package for Social Science) version 23.0, with significance level adopted of p <0.05. The values found for the response speed were: sub-14 was 1.739s, sub-15 was 1.768s, sub-17 was 1.706s and sub-20 was 1.813s. The number of correct answers for the sub-14, sub-15 and sub-17 categories was 51, while in the sub-20 category 54 were correct. Comparisons showed that response time was similar in all categories. (p = 0.162). However, the comparison of the accuracy of response did not differ between the sub-14 x sub-15 (p = 0.391), the sub-14 x sub-17 (0,372) and the sub-15 x sub-17 (p = 1,000) categories. but had a difference of all categories with the sub-20 category (p <0.001). It is concluded that the response time is equal between the categories, while the accuracy of response is better for the athletes of the sub-20 category. Thus, under-20 athletes can make better decisions when they are attentive to the task compared to the other categories